The Effectiveness Of Powtoon Aplication On The Student’s Listening Comprehension At Ma Al-Hijrah Cimaung - nur aliyani, fanny; Nopiyadi, Dwi; Putra darma, Virga (NextGen Education Review Journal, 2025)
This study examines the challenges of teaching English, specifically listening comprehension, at MA Alhijrah Cimaung. Conventional teaching methods often fail to engage students effectively, leading to disinterest and a gap between learning objectives and achievement. To address this, the study explores the integration of technology, specifically the Powtoon app, as an innovative solution to improve the learning process. The research reveals a significant improvement in listening comprehension for students using Powtoon compared to those in the control group using traditional methods. While the effect size is relatively small, this finding provides concrete evidence of Powtoon's potential in enhancing English language learning at the high school level. Incorporating Powtoon into the curriculum at MA Alhijrah Cimaung can greatly benefit students' understanding of narrative text. The study recommends further integration of technology in English language teaching and suggests conducting additional research to explore the impact of technology on student learning. These efforts aim to enhance educational practices and improve the overall quality of education in schools.